Effect of Leadership Style and Compensation on Employee Performance With Job Satisfaction as Intervening Variable (Study at Fatimah Islamic Hospital Banyuwangi) - Suprapto, Suprapto; Sanosra, Abadi; Susbiyani, Arik (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
Fatimah Islamic Hospital Banyuwangi is one of the Muhammadiyah network hospitals in Banyuwangi Regency which has a very important function in efforts to increase the level of health in the Banyuwangi community. Therefore, the performance of hospital employees is very important for achieving overall hospital performance. This study aims to determine the direct and indirect effect of leadership style, compensation on employee performance through job satisfaction on employees of the Fatimah Islamic Hospital in Banyuwangi. This research is a quantitative research. The data collection instrument used a questionnaire which was distributed to 109 respondents. The analysis technique of Structure Question Modeling (SEM) was using the statistical software SmartPLS version 3.0. Based on the research results obtained empirical facts in the form of: (1) Leadership style has a positive and significant effect on job satisfaction of 0.000; (2) Compensation has a positive and significant effect on job satisfaction of 0.002; (3) Leadership style has a positive and significant effect on employee performance of 0.027; (4) Compensation has a positive and significant effect on employee performance of 0.022; (5) Employee job satisfaction has a positive and significant effect on employee performance of 0.020; (6) Leadership style has a positive and significant effect on employee performance with job satisfaction as a mediator of 0.038; (7) Compensation has a positive and significant effect on employee performance through job satisfaction of 0.033.